Efektivitas Media Pembelajaran Flipbook untuk Meningkatkan Motivasi Belajar Siswa Sekolah Dasar - Luthfiyah Luthfiyah; Rahmat Kamal (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2026)
This research was motivated by the decline in students’ interest in batik learning. Batik lessons were generally delivered through conventional teaching methods, supported by limited learning time and very restricted teaching materials, which caused students to be less enthusiastic about participating in classroom activities. To address this problem, teachers introduced flipbook-based learning media as an innovation to create a more effective, efficient, and engaging learning process while supporting the achievement of learning objectives. The purpose of this study was to increase students’ learning motivation through the use of flipbook learning media in batik lessons. This study employed a descriptive quantitative research method involving a sample of 26 students. Data were collected to measure changes in students’ motivation after the implementation of the flipbook media. The findings showed that the use of flipbooks successfully increased students’ learning motivation by 81%, which was categorized as very high. The results indicate that flipbook media can provide a more attractive and interactive learning experience, help students understand batik learning materials more easily, and encourage greater participation during the learning process. Therefore, flipbook learning media can be considered an effective alternative for improving student motivation and supporting more meaningful batik learning in classroom activities.